Perceptions of female students toward hologram video conferencing technology at AOU - M. Aman, Abdulrazak; Shiratuddin, Norshuhada (International Journal of Engineering and Technology, 2020)
The research paper primarily aims at understanding women's discernment in the field of education if it is governed by technology such as hologram video conferencing. The paper is expounded in the context of Saudi Arabâ€™s education system as the country of Saudi Arab is fringed by many rules and regulations for females pursuing higher education. The research paper will extrapolate the change in conventional learning and the ways in which it can benefit womenâ€™s perception and society at large. Arab Open University (AOU) has been a pioneer in distance and e-learning in SA and hence the study is directly directed towards implementing Hologram Video Conferencing and viewing the change in gender biases when it comes to acquiring scientific learning. The paper will also delve into the challenges that can be faced in adoption of holographic based learning and how it can be overcome by changing awareness and deploying more stringent rules by the government.Â